Use of a Hybrid Solar Oven for Houses in Dry Climates: An Experimental Study of Thermal Performance - Buigues Nollens, Arturo (2012)
This paper presents a hybrid solution to problems presented by box-type solar ovens in night and cloudy conditions. The developed hybrid solar oven is supplied with both electric and solar energy and can be used in early morning hours, on cloudy days, or when solar radiation decreases or disappears: The findings from thermal tests and the hybrid performance analysis are presented. The merit figures for F1 and F2 ovens, as well as the cooking power were determined, in accordance with the Ibero-American Network of Solar Cookers guidelines. These experimental results demonstrate that these ovens are suitable for home use in dry climates. The ovens can be implemented and developed as a component of existing government programs and they can supply cheap, reliable power to underpriviledged communities and help to reduce deforestation.